MANAJEMEN LABA (EARNINGS MANAGEMENT) TERHADAP RETURN SAHAM PERUSAHAAN INITIAL PUBLIC OFFERINGS (IPO) NON KEUANGAN DAN NON JASA DI BURSA EFEK JAKARTA - Annisah Febriana (UMSurabaya Publishing, 2014)
This research used data of companies carrying out IPO between 2008 to 2011 and survey period of performance for two years pre and three years post – IPO. Sample was selected purposively and there were 60 companies meeting the requirements as sample of this research, consisting of 30 issuers companies and 30 control companies (non – issuers) in the same period of survey. The control companies were needed to avoid bias from the evaluation model that finally will make the evaluation result more robust (Denis and Sarin, 1999). The result of this research indicated that actually earnings management was conducted by the company during the IPO. The positive value of discretionary accruals before the offering period proved it. Positive discretionary accrual value is indicators that earnings management performed by manager is income increasing in nature. This research also proved that negative correlation between discretionary accruals with the operation performance and stock return. It means that earnings management performed by discretionary accrual before IPO period will decline the performance after the IPO. This research also indicated that declining of issuers performance is higher than non issuers dis. It is proved with the issuer’s average operational performance value and stock return performance that is higher compared to the non issuer’s. it indicated bad performance of the issuers before IPO that triggered to implement earnings management. This result showed opportunistic attitude performed by management’s company with aims to increase the investor’s expectation toward the future performance of the company and to increase the offering price. This opportunistic attitude taken place because of the existing asymmetry information in the IPO process. Keyword : Earnings management, Initial public offerings, Operating performance, Stock return.